A new genus and species of slug caterpillar (Lepidoptera: Limacodidae) from Taiwan - Lin, Yu-Chi; Braby, M.f.; Hsu, Yu-Feng (Zootaxa, 2020)
The genus Epsteinius Lin, Braby & Hsu gen. nov. is established to accommodate a new, diminutive species of limacodid moth, E. translucidus Lin, sp. nov., from central Taiwan. Although the new species is the sister taxon to Microleon Butler, 1885 according to molecular phylogenetic data, it differs fundamentally from that genus in adult morphology, wing color pattern, male and female genitalia, and larval morphology. Larvae of E. translucidus Lin, sp. nov. represent an interesting case in which crypsis is based on transparency through its body color, resting behavior, and feeding pattern.